Răspuns :
{[(2x-3) x 4 - 5 ] x 6 - 7} x 8 - 9 = 271 / +9
{[(2x-3) x 4 - 5] x 6 - 7} x 8 = 280/ : 8
[(2x-3)x4-5] x 6 - 7=35 / +7
[(2x-3) x 4 - 5 ] x 6 = 42 / :6
(2x-3) x 4 - 5 = 7 / +5
(2x-3) x 4 = 12 / :4
2x-3 = 3 / +3
2x = 6 / :2
x = 3
{[(2x-3) x 4 - 5] x 6 - 7} x 8 = 280/ : 8
[(2x-3)x4-5] x 6 - 7=35 / +7
[(2x-3) x 4 - 5 ] x 6 = 42 / :6
(2x-3) x 4 - 5 = 7 / +5
(2x-3) x 4 = 12 / :4
2x-3 = 3 / +3
2x = 6 / :2
x = 3
{[(2x-3)4-5]6-7}8-0=271
{(8x-12-5)6-7}8-9={(8x-17)6-7}8-9=(48x-102-7)8-9=(48x-109)8-9=384x-872=9
384x=9+872
384x=891
x=891/384
{(8x-12-5)6-7}8-9={(8x-17)6-7}8-9=(48x-102-7)8-9=(48x-109)8-9=384x-872=9
384x=9+872
384x=891
x=891/384